Culture Entrenched Gender Inequality in Othello by William Shakespeare and Night of No Moon by Syed Waliullah: A Comparative Study - Kabir, K.M. Wazed; Israt, Kashfia (Advances in Social Sciences Research Journal, 2022)
Culture of a society directly influences the pattern of behavior of the people. It is such a strong force that, people are hardly able to go and think beyond the boundary of their cultural practices. The problem begins when cultural indoctrination controls human thought process and appears to justify inhuman practices in the name of culture and tradition. This study has been done with a view to exposing the gender-based inequality prevailing in the society which is nurtured by culture. In doing so Othello by William Shakespeare and Night of No Moon by Syed Waliullah, two great pieces of literary works have been picked. Both of the literary pieces depict unequal treatment of the women in the society. Although, two of them are composed in different contexts, yet there are similarities in terms of treatment of females in the society. In both Othello and Night of No Moon the fate of women is decided by the men and the whole societal system fuels the unjust action. The authors draw real life characters to show how the females become victims in the hand of social organizations formed and dominated by men. This study explores through the characters and plots of the two texts and intends to see the facts from a feminist point of view to analyze behavior of people. Therefore, we observe the condition of women of the society, who are considered as ‘the weaker sex’, and continuously dominated, suppressed and victimized by culturally motivated men. Thus, we have put our logical argument drawing evidences from the literary texts to establish that, Culture of a society substantially contributes to constitute patriarchal mindset among the people of the society which results in treating women as so called ‘Second sex’.